Small reservoirs in the northern regions of Ghana and their vulnerability to drying - Siabi, Ebenezer K.; Akpoti, Komlavi; Zwart, Sander J. (International Water Management Institute (IWMI). CGIAR Initiative on Aquatic Foods, 2023)
This study investigates the dynamics and susceptibility to drying of small reservoirs in Northern Ghana, leveraging advanced machine learning and remote sensing techniques through Google Earth Engine. It aims to map these reservoirs, evaluate their extent, and analyze water availability during dry seasons, crucial for understanding water resource potential for aquaculture and supporting food security goals under the CGIAR Initiative on Aquatic Foods. Findings reveal a consistent decrease in the number and size of reservoirs from November to April, attributed to increasing dry conditions, with a notable rise in reservoir numbers peaking in November 2022. Small reservoirs (< 0.6 hectares) were found to be more numerous than medium and large ones, predominantly located in midstream areas. Approximately half of these reservoirs face a very high risk of drying, highlighting the urgent need for effective water management strategies. This research provides significant insights into the vulnerabilities of small reservoirs, guiding sustainable management practices to combat the impacts of climate change and environmental stressors on water and aquaculture resources in Northern Ghana.